Assessing risk factors for severe forms of COVID‐19 in a pregnant population: A clinical series from Lombardy, Italy. Issue 2 (26th November 2020) - Di Martino, Daniela; Chiaffarino, Francesca; Patanè, Luisa; Prefumo, Federico; Vergani, Patrizia; Ornaghi, Sara; Savasi, Valeria; Spinillo, Arsenio; Cromi, Antonella; D'Ambrosi, Francesco; Tassis, Beatrice; Iurlaro, Enrico; et al.
Abstract : In 250 pregnant women with either asymptomatic, non‐severe, or severe SARS‐CoV‐2 infection, obesity turned out to be the main determinant of severe COVID‐19 illness.